Focal Ballismus (Right Arm) in a Boy with Wilson's Disease - Koul, Roshan; Vijay, Priti; Khanna, Rajeev; Alam, Seema (Journal of Pediatric Neurology, 2020)
Ballismus is defined as rapid, forceful, shaking or throwing involuntary movement of the extremities, mainly proximal parts. When it affects half of the body (upper and lower limbs on one side), it is called hemiballismus. If it affects one limb, it could be labeled as focal or one limb ballismus. Any lesion (vascular, trauma, tumor, deposition, and demyelination) in the subthalamic nucleus of the basal ganglia results in ballismus. A rare entity such as copper deposition in Wilson's disease can manifest as ballismus. In this case report, we described a boy with Wilson's disease with focal ballismus of the right arm.
Keywords: chorea; dystonia; ballismus; Wilson's disease